Development of a novel UWB planar antenna using a genetic algorithm - Fertas, Khelil; Kimouche, Hocine; Challal, Mouloud; Ghanem, Farid; Fertas, Fouad; Aksas, Rabia (2017 5th International Conference on Electrical Engineering - Boumerdes (ICEE-B), 2017)
This paper introduces a new design and optimization method of ultra wide band (UWB) printed antenna using a genetic algorithm (GA). The proposed antenna consists of a radiating patch element with an area divided into 2 mm square cells where each cell is allocated by either conducting or nonconducting property. The presented antenna is designed to operate from 2.4 GHz to 9.8 GHz. Numerical results for the return loss, radiation pattern and gain of the antenna are presented and discussed. The introduced antenna was fabricated, and the measured results are in good agreement with the full-wave simulated ones.